Sleep bruxism increases the risk for painful temporomandibular disorder, depression and non-specific physical symptoms - Fernandes, G. [UNESP]; Franco, A. L.; Siqueira, J. T. T.; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Camparis, Cinara Maria [UNESP] (Wiley-Blackwell, 2012)
To explore the relationship between sleep bruxism (SB), painful temporomandibular disorders (TMD) and psychologic status in a cross-sectional study. The sample consisted of 272 individuals. The Research Diagnostic Criteria for TMD (RDC/TMD) was used to diagnose TMD; SB was diagnosed by clinical criteria proposed by The American Academy of Sleep Medicine. The sample was divided into four groups: (1) patients without painful TMD and without SB, (2) patients without painful TMD and with SB, (3) patients with painful TMD and without SB and (4) patients with painful TMD and with SB. Data were analysed by Odds Ratio test with a 95% confidence interval. Patients with SB had an increased risk for the occurrence of myofascial pain (OR = 5.93, 95% CI: 3.1911.02) and arthralgia (2.34, 1.583.46). Group 3 had an increased risk for moderate/severe depression and non-specific physical symptoms (10.1, 3.6727.79; 14.7, 5.3939.92, respectively), and this risk increased in the presence of SB (25.0, 9.6564.77; 35.8, 13.9491.90, respectively). SB seems to be a risk factor for painful TMD, and this in turn is a risk factor for the occurrence of higher depression and non-specific physical symptoms levels, but a causeeffect relationship could not be established.
Keywords: arthralgia; depression; facial pain; risk groups; sleep bruxism